Desenvolvimento de ferramentas moleculares para elucidação de mecanismos de ajustes fisiológicos do pacu submetido a jejum - Squassoni, Gustavo Henrique [UNESP] (2015)
The Brazilian aquaculture is as a commercial activity on the rise. Among the native species, pacu, Piaractus mesopotamicus, stands out as one of the most reared in the southern, central and northeastern Brazil. However, similar to what occurs with other commercial species, the production of pacu experience problems during the production process, such as high population density used, incorrect food supply and stress, resulting in reduced productivity and increased mortality. One of the strategies investigated to improve the management of fish feeding is the use of dietary restrictions for a certain time to promote growth compensation during the refeeding period. However, information related to physiological responses and cell modulations caused by this type of management are still unknown. Understanding this information is necessary for the development of strategies to minimize the stress caused by food restriction. The purpose of this study was to evaluate the impact of prolonged fasting, followed by short refeeding on the physiological parameters, gene expression related to growth and stress, the prevalence of certain bacterial groups in the mucosa and intestinal content and cloning, identification and validation of reference genes for normalization of gene expression data in studies with pacu. The results showed that the pacu has great capacity for mobilization of endogenous reserves, but their recovery is faster in smaller fish. This study presents the first experimental comparisons for validation of reference genes for pacu. Cloned, sequenced and validated genes will be used in future studies of gene expression with this species. In addition, this study provides the first information about the changes in intestinal microbiota in pacu. The use of qPCR for the detection and quantification of specific bacterial groups proved to be an important tool for assessing changes in bacterial communities in the mucosa and intestinal contents of fish